Decentralized secondary control for frequency restoration and power allocation in islanded AC microgrids - Lian, Zhijie (2023)
In this paper, we show that a fully decentralized simple control method can be used to solve the secondary frequency restoration and power allocation problem in AC microgrid (MG) systems. Compared to communication enabled control schemes, this paper makes a breakthrough of realizing frequency restoration under a decentralized secondary control by which no data exchanging process happens and thus, MG reliability and robustness can be enhanced. Different from most of existing decentralized control approaches, rigorous theoretical analysis proves that the proposed simple decentralized controller, which is easier for implementation, can still ensure the stability of the overall AC MG system, achieve frequency restoration and accurate optimal power sharing flexibly. In order to illustrate the proposed scheme, real-time tests are carried out in an islanded AC MG system built in the real-time simulator OPAL-RT. The results do show its effectiveness and also verify the established theoretical findings.